(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, and prayers and peace be upon our master Muhammad, and upon his family and companions, and afterThe Holy Qur’an cannot be properly understood except by relying on the Arabic tongue.God Almighty honored this noble language, making it the language of the clear verses, and the evidence of His incomparable miracle.It breaks down over the ages and years.It is known that Arabic is the mainstay of religion and one of the important pillars of Islamic culture.Every commentator, mujtahid, or jurist, indeed every scholar, can take one step without going back.into Arabic, and it became known to all Sharia scholars that one of the first prioritiesThe researcher is fluent in the Arabic language and understands it in a comprehensive manner. The sources spoke about theseNahiyyah, especially the books of exegesis and introductions to it, books of fundamentals, books of the sciences of the Qur’an, and books ofrhetoric, and we wanted, through this brief research, to contribute our role in showing this aspectvital in a graceful scientific garb far from obscene brevity and boring digressions.It helps us to serve his dear book that he is all-hearing and answering.Everyone who wants to understand the Holy Qur’an must have some knowledge of it.The basic conditions, and on the basis of these conditions stands the knowledge of the Arabic in which the Qur’an was revealed.The Holy Qur’an emphasized that his style was Arabic in many verses.Arabic tongue, and that it is an Arab judgment, and that it is an Arab comparison, and this has reached eleven places onSpecifically, (1).